Resilience-focused debriefing: addressing complexity in interprofessional simulation-based education—a design-based research study - Torben Nordahl Amorøe; Hans Rystedt; Lena Oxelmark; Peter Dieckmann; Paulin Andréll (Advances in Simulation)
Abstract Background Healthcare students are taught teamwork and collaboration through interprofessional simulation-based education (IPSE). However, the complex nature of healthcare and the ability to react resiliently to the unexpected is usually not actively addressed. This study explores how complexity and resilience can be addressed in IPSE debriefing for pre-graduate healthcare students. Methods A focus group of nine facilitators in an IPSE course for nursing and medical students was introduced to the characteristics of complex systems, Safety-II, solution-focused approach, and appreciative inquiry. In five iterations, the facilitators discussed how these theories and methods could be applied, tested, evaluated, and adjusted in debriefings supported by video clips of their own debriefings. Video recordings of debriefings (n = 56) and focus group interviews (n = 6) were collected. Focus group interviews were transcribed and reviewed to explore the basis for final recommendations. Results Facilitators identified and tested 22 debriefing techniques that potentially could address complexity and resilience in IPSE. In total, 17 of the tested techniques were found to be able to make students aware of the complex nature of interprofessional teamwork and collaboration in acute dynamic healthcare situations, their existing capacities for resilience, potentially increasing their capacity for resilience. Conclusions Learning needs around resilience and complexity could be addressed successfully in IPSE debriefings, but further studies are needed to assess the effect of resilience-focused debriefing techniques on teamwork in IPSE.